The Effect of Malicious Cyber Activity on the US Corporate Sector - Anna Scherbina; Bernd Schlusche (American Enterprise Institute (AEI), 2023)
We compile a comprehensive dataset of adverse cyber events experienced by U.S. firms. We then categorize cyber incidents by their detrimental impacts on firms' assets and operations and show that firms suffer significant value losses across multiple cyber categories. These losses also spill over to economically linked firms, thereby amplifying the negative effect of malicious cyber activity on the economy. We additionally assemble a lexicon to identify from public sources firms that possess trade secrets, work on emerging technology or critical infrastructure projects, or have government and defense contracts, and show that such firms face a higher risk of a cyber incident.
Keywords: 330; Cyberattacks; Malicious Cyber Activity; Cyber Threat Actors; Attack Vectors; Intellectual Property Theft; Trade Secrets; Critical Infrastructures; Emerging Technologies; De-fense Contracts; Government Contracts; Spillover Effects; Economically Linked Firms; CorporateTransparency